Smart Knee Implants and Functional Outcome for Total Knee Arthroplasty - Gordon, Adam M.; Vatti, Lohith; Mont, Michael A. (The Journal of Knee Surgery, 2025)
Smart knee implants integrate advanced sensor-based technologies, forming a unique technology-embedded total knee arthroplasty (TKA) implant. Such implants introduce the ability to capture new elements of patient-related data for use in the context of recovery in real time including subjective reported outcomes and objective outcomes related to range of motion, and gait parameters. This technology allows for real-time data capture and patient-specific insights, creating opportunities to optimize postoperative care. This brief narrative review discusses the foundations and origin of technology-embedded implants, beginning with research-related roots relating to the derivation of fundamental knee joint force measurements. Analyzing the current market of implants, the present review investigates the technological capacities of modern designs including form and function. Further discussed is an evaluation of smart knee implant effectiveness, focusing on its impact on recovery outcomes such as patient-reported outcome measures (PROMs), functional improvement, gait patterns, and patient adherence/satisfaction. Smart implants represent a significant technological advancement in personalized care, leveraging real-time data including joint motion, alignment, and patient motion to assist surgeons in optimizing rehabilitation protocols. These implants provide insights into recovery progression postoperatively, with the potential for early identification of at-risk individuals. Preliminary studies demonstrate favorable patient outcomes and satisfaction, although further research is necessary to establish the long-term benefits and efficacy of smart knee implants.
Keywords: Total Knee Arthroplasty; functional outcomes; sensors; smartphone applications; range of motion